Features of Language Exploration in Japanese Dokkai Authentic Materials: SFL-based Analysis - Novia Hayati; Muthi Afifah; Via Luviana Dewanty; Susi Widianti; Jeni Putra (Chi e Journal of Japanese Learning and Teaching, 2026)
This study examines the linguistic features of Japanese product packaging texts, focusing on beverages, medicines, and instant noodles. Using a qualitative case study design, it analyzes 30 authentic Japanese labels to identify naturally occurring language features relevant to beginner-level Japanese learners. The analysis reveals eight linguistic features in beverage labels and ten features each in medicine and instant noodle packaging. Across all categories, packaging texts rely on nominalization, technical labels, scientific terminologu, numerical data, and dense noun-based structures to convey precise and regulated information. Interpersonally, polite imperatives, evaluative expressions, honorific forms, and cosumer-oriented phrases reflect Japanese communicative norms. Textually, list structures, discourse markers, and parallel formatting contribute to clarity and efficient information processing. At the same time, each category shows distinct rhetorical tendencies: beverage packaging employs persuasive and hybrid Japanese English expressions, medicine packaging foregrounds safety and scientific neutrality, and instant noodle packaging combines instructional sequencing with promotional language. The findings show that Japanese packaging texts function as hybrid genres integrating descriptive, procedural, and persuasive meanings. Their linguistic density, functional organization, and cultural relevance indicate strong potential as authentic dokkai materials in genre-based pedagogy for beginner-level Japanese reading and writing instruction.